Probiotics as control for luminescent vibriosis in mud crab (Scylla serrata forskal, 1775) larval rearing. - Candelaria, Patricia M. (College of Fisheries, U. P. in the Visayas, 2010)
Luminescent vibriosis caused by Vibrio harveyi is a common disease problem in mud crab (Scylla serrate) larval rearing. The use of antibiotics to treat vibriosis in mud crab larvae is not apparently viable due to drug resistant vibrios. The use of commercial probiotics to control luminescent vibriosis has been identified as a promising approach. Three experiments were individually carried out to determine the survival rate of mud crab larvae treated with three different commercial probiotics that were inoculated in the rearing water used to rear mud crab larvae. To determine the effect of commercial probiotics on heterotrophic count (THC), presumptive vibrio count (PVC), yellow colony-forming Vibrio count (YCFVC), green colony-forming Vibrio count (GCFVC) and luminous Vibrio count (LVC), rearing water and mud crab larvae samples were collected, spread-plated and counter on nutrient agar plates with 1.5% NaCI and thiosulfate-citrate bile salt (TCBS) agar plates, respectively. Water quality parameters were also monitored to determine the effects of probiotics on the level of salinitytemperature, dissolved oxygen, pH, ammonia and nitrite. Further, the survival rate of probiotic treated and untreated mud crab zoea larvae were determined through immersion challenge with V. harveyi. Addition of commercial probiotics in the rearing water did not significantly reduce LVC in the rearing water and mud crab larvae compared with the control. However, these probiotics significantly improved water quality as indicated by marked reduction in ammonia and nitrite levels. In addition, probiotic treated mud crab larvae challenged with V. harveyi resulted in higher survival rates indicating that application of commercial probiotics during mud crab larval rearing is a strategy to control unwarranted outbreaks of luminescent vibriosis in mud crab larval rearing.